Words that matter : how the news and social media shaped the 2016 presidential campaign /: how the news and social media shaped the 2016 presidential campaign. ([2020]) - Bode, Leticia; Budak, Ceren; Ladd, Jonathan M; Newport, Frank; Pasek, Josh; Singh, Lisa O; Soroka, Stuart N; Traugott, Michael W
No abstract available